Application of wireless heart rate system in men's freestyle - Zhao, F.; Liu, Y.; Zhou, Y. (Exercise Biochemistry Review, 2018)
Objective Using heart rate wireless system to continuously track the morning pulse of male freestyle wrestlers after different training loads. The basic value of individual morning pulse and the interval of variation of individual morning pulse after class were established for the elite players.